IMPLEMENTASI SENSOR MQ-2 SEBAGAI ALAT DETEKSI ASAP ROKOK MENGGUNAKAN ATMEGA328 - Arif Setia Sandi A; Imam Ahmad Ashari; Retno Agus Setiawan; R Bagus Bambang Sumantri (Universitas Methodist Indonesia, 2021)
Smoking is an activity that can make addiction a habit every day, because cigarettes contain substances that are harmful to the user's body and to other people who inhale the smoke. Included in the school environment, several factors that increase interest in cigarettes among students are the factor of wanting to try, being influenced by friends and the environment. The school environment has a big impact, with rules and regulations that are not enforced to the maximum resulting in an increasing number of cigarette users among students. this can affect the friends around him. From these problems, the authors conducted research using Arduino Uno as the main component in the development of the Cigarette Smoke Detection Tool which was combined with the MQ-2 sensor as a module used for cigarette smoke detection, and the module will sound a buzzer when it detects cigarette smoke, then combined with the module. GSM as a tool to notify a predetermined number when cigarette smoke is detected in the room via SMS (Short Message Service). The result of this test is that the MQ-2 sensor can detect if there is cigarette smoke around the sensor or device at a short distance of less than 6 meters.